CT and MRI in the diagnosis of epilepsy: methods, findings and possibilities. Literature review - Kučinskas , L.; Jurkevičiūtė , G.; Gleiznienė , R. (Neurologijos seminarai, 2018)
Epilepsy is a chronic disorder of the brain that causes different types of seizures. Neuroimaging is essential in determining the etiology of seizures. The most common neuroimaging studies are CT and MRI. CT is performed after the first seizure to exclude acute or life threatening conditions. CT is informative in detecting encephalomalacia, intracranial haemorrhage, calcification, and bone lesions. MRI has a greater value than CT in epilepsy diagnosis. MRI detects hippocampal sclerosis, cortical development abnormalities, gliosis, vascular malformations, brain tumors, etc. In addition, MRI is a necessary part of presurgical examination of drug-resistant epilepsy patients.